Epidemiology of basal cell carcinoma in the United Kingdom: incidence, lifestyle factors, and comorbidities - Reinau, D (Nature Publishing Group, 2014)
BACKGROUND: Little is known about the epidemiology of basal cell carcinoma (BCC). METHODS: Using the Clinical Practice Research Datalink, we calculated annual incidence rates. In a case–control analysis, we examined lifestyle factors and comorbidities. RESULTS: Incidence rose significantly between 2000 and 2011. Basal cell carcinoma risk was increased in alcohol drinkers (slightly) and immunocompromised patients, but reduced in smokers and individuals with abnormal weight. CONCLUSIONS: Basal cell carcinoma places a growing public health burden. Lifestyle factors do not play a major role in pathogenesis, but immunosuppression is important.